2019
DOI: 10.1007/s00420-019-01475-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between recovery experiences and well-being among younger and older teachers

Abstract: Purpose The study had three aims. We investigated, first, how six recovery experiences (i.e., detachment, relaxation, control, mastery, meaning, and affiliation) during off-job time suggested by the DRAMMA model (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 90 publications
1
38
0
4
Order By: Relevance
“…Recent qualitative research using a best possible selves paradigm (Loveday et al 2018b) showed that affiliation was considered the most important ingredient participants described when envisioning their ideal future and that meaning also played a role in living a good life (Loveday et al 2018a). Similarly, Virtanen et al (2019) found that meaning and affiliation were positively related to life satisfaction among schoolteachers and principals.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recent qualitative research using a best possible selves paradigm (Loveday et al 2018b) showed that affiliation was considered the most important ingredient participants described when envisioning their ideal future and that meaning also played a role in living a good life (Loveday et al 2018a). Similarly, Virtanen et al (2019) found that meaning and affiliation were positively related to life satisfaction among schoolteachers and principals.…”
Section: Discussionmentioning
confidence: 88%
“…To the best of our knowledge, the DRAMMA model's needs (detachment, relaxation, autonomy, mastery, meaning and affiliation) have so far been studied together only in two cross-sectional quantitative studies. Virtanen et al (2019) examined the DRAMMA model among 909 school teachers and principals. Relaxation, mastery, control and detachment related positively to vitality, and control, meaning, detachment and affiliation related positively to life satisfaction, suggesting that all DRAMMA needs play a role in well-being (Virtanen et al 2019).…”
Section: Relations Between Dramma Need Satisfaction and Optimal Functmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most direct consequences of the lack of recovery of work is the loss of energy (Siltaloppi et al, 2009;Virtanen et al, 2020). However, could the opposite relationship occur?…”
Section: Daily Energetic Resources As Antecedents Of Recovery From Workmentioning
confidence: 99%
“…In this sense, some researchers have called for studies to discover how workers who show high levels of work engagement recover from job stress (van Wijhe et al, 2013). Second, this study contributes to the study of specific moderating variables in the recovery process (Steed et al, 2019), exploring the moderating role that emotional job demands may have in the relationship between vigor and recovery experiences (Virtanen et al, 2020;Xanthopoulou et al, 2018). Moreover, we analyze our hypothesis using a diary study, which constitutes one of the best designs to collect the dynamics involved in the recovery processes (Demerouti et al, 2009) because it allows the study of the antecedents and moderating factors in short intervals of time.…”
Section: The Dark Side Of Vigor On Recovery In Demanding Workdaysmentioning
confidence: 99%